The Effect of Mini Boiler Fire Pipe Diameter Variations on Steam Power and Efficiency - Mochamad Vicky Fadli; A’rasy Fahruddin (Procedia of Engineering and Life Science, 2021)
Boileri isi ai heati machinei (i thermali engineringi )i thati transfersi chemicali energyi ori automatic energyi intoi motion.i Boileri alsoi hasi twoi variationsi ini itsi shape,i therei arei verticali boileri andi verticali boiler. Ini thei operationi ofi ai boileri iti cani alsoi causei severali dangers,i includingi poisoni gas,i pressurei explosion, fire,i etc.i Oni thei insidei ofi thei boileri tubei therei isi ai firei pipelinei thati leadsi toi thei chimney,i thisi firei pipei servesi toi helpsi flowi heati fromi thei furnacei toi thei endi ofi thei tube,i soi asi toi shorteni thei timei to heat a boiler.i Thei purposei ofi thisi researchi isi toi determinei thei ratioi ofi thei highesti efficiencyi andi steam poweri valuesi byi experimentingi withi variationsi ofi thei firei pipei usingi ai 10i mmi firei pipei diameter,i 15i mmi firei pipei diameter,i andi 20i firei pipei diameter.